Disaster Management and the Urban Poor in Ahmedabad, India - Yu, Jessica (My University, 2015)
BACKGROUND: The World Bank report warns that the poor living in informal settlements and slum conditions are the most likely to be killed or harmed by extreme weather. They are morevulnerable to disasters often due to clogged drains, land subsidence, heat waves, and increased health risks. Disaster management (DM) in slums is part of a larger development problem in developing countries. However, analytical literature on the exact link and nature of problemsfaced by slum dwellers due to climate change and disasters is scarce. More research is needed to address the gap in literature between increasing urbanisation and the implications for the urban poor in disaster management plans (DMPs). METHODOLOGY: This research was granted approval by the Hamilton Health Sciences ResearchEthics Board on May 28, 2014. In June 2014, semi-structured interviews and focus groups were conducted, including 24 interviews and 9 focus groups with community members (CMs), 12 interviews with key informants from organisations in the civil society (CSOs), and 3 interviews with Government officials (GOs). The interviews and focus groups were transcribed verbatim (to the extent possible) and imported into NVivo 10 (QSR International) for qualitative content analysis. RESULTS: Five key points were made by participants in the focus groups and interviews: 1.) Some physical and non-physical infrastructure needs were not considered by GOs and CSOs for slum upgrading, such as the repair of shelter roofs and the creation of self-formed slum groups, 2.) Bottom-up participation and citizen engagement needed to be improved during the design and implementation of DMPs, 3.) Communication was pertinent during all phases of the DM cycle, including multisectorial involvement from all three stakeholder groups, 4.) Different barrierswere raised, including urbanization and planning, which affected the required participation and communication in DM, and 5.) Even substantial levels of water in the home at 3-4 inches high were described as waterlogging rather than flooding, suggesting that disasters were being normalised. DISCUSSION AND CONCLUSION: By describing different measures and approaches that are used for and by the urban poor, new DM strategies are suggested (such as scaling up and including new components in Slum Upgrading Programs). Several recommendations were made to improve DM planning, including the need to overcome several barriers and the potential of formulating contextual DMPs (such as an Earthquake Action Plan). A novel finding was the apparent normalisation of disasters. This raises important questions about how disasters are framed in Ahmedabad and the policy solutions that result from it. Climate change was seldom noted, even though it is expected to increase the frequency and intensity of future disasters. These findings can be considered for policy makers in megacities around the world and in the post-2015 Millennium Development Goals and Hyogo Framework of Action.
Keywords: Disaster Management; Global Health; Slum Health; Ahmedabad Disaster; Disaster Management Planning; City Disasters